Treatment for chronic low back pain: the focus should change to multimodal management that reflects the underlying pain mechanisms. (3rd July 2017) - Müller-Schwefe, Gerhard; Morlion, Bart; Ahlbeck, Karsten; Alon, Eli; Coaccioli, Stefano; Coluzzi, Flaminia; Huygen, Frank; Jaksch, Wolfgang; Kalso, Eija; Kocot-Kępska, Magdalena; Kress, Hans-Georg; Mangas, Ana Cristina; et al.
Abstract: Chronic low back pain: Chronic pain is the most common cause for people to utilize healthcare resources and has a considerable impact upon patients' lives. The most prevalent chronic pain condition is chronic low back pain (CLBP). CLBP may be nociceptive or neuropathic, or may incorporate both components. The presence of a neuropathic component is associated with more intense pain of longer duration, and a higher prevalence of co-morbidities. However, many physicians' knowledge of chronic pain mechanisms is currently limited and there are no universally accepted treatment guidelines, so the condition is not particularly well managed. Diagnosis: Diagnosis should begin with a focused medical history and physical examination, to exclude serious spinal pathology that may require evaluation by an appropriate specialist. Most patients have non-specific CLBP, which cannot be attributed to a particular cause. It is important to try and establish whether a neuropathic component is present, by combining the findings of physical and neurological examinations with the patient's history. This may prove difficult, however, even when using screening instruments. Multimodal management: The multifactorial nature of CLBP indicates that the most logical treatment approach is multimodal: i.e. integrated multidisciplinary therapy with co-ordinated somatic and psychotherapeutic elements. As both nociceptive and neuropathic components may be present, combining analgesic agents with different mechanisms of action is a rational treatment modality. Individually tailored combination therapy can improve analgesia whilst reducing the doses of constituent agents, thereby lessening the incidence of side effects. Conclusions: This paper outlines the development of CLBP and the underlying mechanisms involved, as well as providing information on diagnosis and the use of a wide range of pharmaceutical agents in managing the condition (including NSAIDs, COX-2 inhibitors, tricyclic antidepressants, opioids and anticonvulsants), supplemented by appropriate non-pharmacological measures such as exercise programs, manual therapies, behavioral therapies, interventional pain management and traction. Surgery may be appropriate in carefully selected patients.